2022
DOI: 10.3389/fpls.2022.886805
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics Analyses of Two Sorghum Cultivars Reveal the Molecular Mechanism of Salt Tolerance

Abstract: Sorghum [Sorghum bicolor (L.) Moench] is one of the most important cereal crops and contains many health-promoting substances. Sorghum has high tolerance to abiotic stress and contains a variety of flavonoids compounds. Flavonoids are produced by the phenylpropanoid pathway and performed a wide range of functions in plants resistance to biotic and abiotic stress. A multiomics analysis of two sorghum cultivars (HN and GZ) under different salt treatments time (0, 24, 48, and 72) was performed. A total of 45 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
3
12
0
Order By: Relevance
“…Cis-acting element analysis indicated that PUB genes might participate in diverse biological processes, especially in response to salt stress. Flavonoid biosynthesis was the major pathway of sorghum salt tolerance in our previous study, while MYB-binding elements are important regulators of avonoid biosynthetic genes in plants [33,54]. We found 12 SbPUB genes contained the MYB-related elements, which also exhibited diverse levels of expression in the proteomic analysis.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Cis-acting element analysis indicated that PUB genes might participate in diverse biological processes, especially in response to salt stress. Flavonoid biosynthesis was the major pathway of sorghum salt tolerance in our previous study, while MYB-binding elements are important regulators of avonoid biosynthetic genes in plants [33,54]. We found 12 SbPUB genes contained the MYB-related elements, which also exhibited diverse levels of expression in the proteomic analysis.…”
Section: Discussionmentioning
confidence: 64%
“…Several studies have found that the PUB gene family is involved in salt tolerance. To explore the functions of the PUB gene family in sorghum, we detected the expression levels of SbPUBs based on the salt tolerant proteomic data for two sorghum cultivars obtained in our previous study; we found that the pathways of avonoid biosynthesis and ubiquitin-mediated proteolysis may play important physiological roles in sorghum salt tolerance [33]. Based on the proteomic results, 18 differentially expressed PUB family genes, belonging to different subfamilies, were identi ed as having clearly differential expression (Fig.…”
Section: Expression Analysis Of Sbpub Genes Under Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted using the NEBNext ® UltraTM RNA Library Prep Kit for Illumina ® (NEB, USA) following manufacturer's recommendations. The purity, concentration and integrity of RNA were assessed using a NanoPhotometer ® spectrophotometer (IMPLEN, CA, USA), Qubit ® RNA Assay Kit in Qubit ® 2.0 Flurometer (Life Technologies, CA, USA) and RNA Nano 6000 Assay Kit of the Bioanalyzer 2100 system (Agilent Technologies, CA, USA), respectively (Ren et al, 2022). One mg high quality RNA per sample was then used to construct the cDNA library, and was sequenced using an Illumina HiSeq sequencing platform by Metware Biotechnology Co., Ltd. (Wuhan, China).…”
Section: Measurement Of Mda and H 2 O 2 Levels And Activities Of Anti...mentioning
confidence: 99%
“…The samples described above were also used in the metabolomics analysis. The extract analysis, and the identification and quantification of metabolites were performed by MetWare (Wuhan, China) using standard procedures and based on a previously published protocol (Sun et al, 2020;Ren et al, 2022). Briefly, the freeze-dried roots were crushed using a grinder (MM 400, Retsch) at 30Hz for 1.5 min.…”
Section: Widely-targeted Metabolomics Analysismentioning
confidence: 99%